Spectral Domain Optical Coherence Tomographic Findings of Bietti Crystalline Dystrophy - Ali Osman Saatci; Hasan Can Doruk; Aylin Yaman; Ferit Hakan Öner (Journal of Ophthalmology)
We analyzed the OCT features of 24 eyes of 12 patients with Bietti crystalline dystrophy (BCD) with the Heidelberg HRA2-OCT. Seventeen of 24 eyes were in intermediate stage of the disease and seven in advanced stage of the disease at the time of latest OCT examination performed in 2014. Outer retinal tubulations and retinal hyperreflective dots were present in 20 of 24 eyes. The remaining four eyes had advanced disease with very thin retina. Appearance of bright plaque on top of RPE-Bruch membrane was present in all eyes. Choroidal hyperreflective spots were noted in 19 of 24 eyes. The remaining five eyes had advanced disease stage with very thin choroid. Mean central macular thickness was 163.08 μm ± 62.52 for all eyes (170.35 μm ± 56.46 in eyes with intermediate disease and 145.42 μm ± 77.2 in eyes with advanced disease). Mean subfoveal choroidal thickness was 95.37 μm ± 55.93 for the study eyes (116.47 ± 46.92 μm in eyes with intermediate disease and 44.14 μm ± 42.43 in eyes with advanced disease). Choroidal hyperreflective spots were noted in 21 of 24 eyes (87.5%). SD-OCT shows the disease progression in retinal and choroidal layers delicately in eyes with BCD and expands our knowledge about the ongoing disease process.